Estádio de desenvolvimento do milho. 2. Efeito sobre o consume e a digestibilidade da silagem em ovinos - Lavezzo, Otávia Elisa Nogueira Mendes [UNESP]; Lavezzo, Wagner [UNESP]; De Siqueira, Edson Ramos [UNESP] (My University, 1997)
Corn plants were ensiled at the milk, milk-early dough, medium dough, and semi-hard dough stages. The intake and digestibility trials showed that: a) silage DM and NFE contents increased and ADF, cellulose, and lignin contents decreased with plant maturity; b) corn plant maturity had little effect on the digestibility of the silages, but the milk and medium dough stages produced the best results; c) no consistent effect of maturity was observed in DM and CP daily intakes (mean values 41.86 and 26.77/ g/kg75, respectively). Nevertheless, daily digestible dry matter and digestible protein intakes (g/kg.75) were higher with medium-dough grains (31.74 and 1.97g, respectively) than with the milk (23.27 and 1.45g, respectively) and the milk-early dough stages (22.60 and 1.28g, respectively). However, similar intakes were observed with the medium-dough and semi-hard dough stages. Total digestible nutrient contents of the silages were affected little by corn plant maturity. Nevertheless, statistical differences were found between the medium dough (70.09%) and the milk-early dough stages (63.07%).
Stage of corn development. 2. Effect upon sheep voluntary intake and digestibility of the silage
Keywords: Corn; Digestibility; Intake; Maturity; Silage